Design & Development of traffic control system for small road of single vehicle flow - Nurul Fitri Binti Parman (2023)
The scheme of traffic lights ensures a smooth flow of road with safety as a concern for vehicle users at small/narrow road with blind spot. One of the most critical consequences of this small/narrow road problems is can cause collision between two vehicles and have to decide which vehicle will use the road first if there are two vehicles getting stuck in the middle of the small/narrow road. Malaysia is one of the highest rates of traffic accident and this issue should be solved to reduce the traffic road accident. The traffic control system at small road of single vehicle flow should be implemented to achieve the objective of this project which are to design a logic to control the flow of the traffic for single road of single vehicle flow and also to design the indicator system to tell the road users who is taking turn to use the road.